Optimalisasi Hasil Belajar Peserta Didik Dengan Memanfaatkan Lingkungan Sekolah Sebagai Sumber Belajar IPA - Oprida, Maria Apriyanti; Yuli Mira Syafriati; Mariana Sada (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The learning process can use the surrounding environment as a learning resource with a view to optimizing student learning outcomes on ecosystem materials. This research is classroom action research (CAR) which is made in 2 cycles where each cycle consists of 4 stages, namely planning, action, observation and reflection. The materials used are class VII-B students with a total of 26 students. The results showed that from cycle I to cycle II, student learning outcomes increased. The percentage of passing learning outcomes in the first cycle is 65% and the average grade is 67, while in the second cycle it is 88% and the average grade is 87. learning increased by 20 points. Utilizing the environment as a learning medium can make teaching and learning activities more memorable, because students are faced with real situations. The lessons learned by students will be more concrete, more precise, and their authenticity will be accountable so that it can be concluded that learning by using the environment as a learning resource can improve student learning outcomes.